Settlement of the Cross-Country Cooperation Agreement between PT. Indah Logistik and City Cargo - Muson, Manuel; Aprilyanti, Siti Laras (PT FORMOSA CENDEKIA GLOBAL, 2025)
Logistics activities are not only focused on a particular area, but the movement of goods also crosses national borders. Indonesia and Saudi Arabia cooperate reasonably in religious activities, especially the Hajj and the Umrah. Millions of Indonesian citizens are estimated to carry out Umrah and Hajj worship activities yearly. This activity not only focuses on the movement of people but also the movement of goods, namely all the needs ranging from food and equipment that must be sent from Indonesia to Saudi Arabia, as well as vice versa, the luggage of Indonesian citizens who have completed the Hajj and Umrah. PT Indah Logistik, one of the logistics companies, sees the potential or opportunity from this movement of goods, but is experiencing obstacles with operational activities in Saudi Arabia. To run this opportunity, PT Indah Logistik collaborates with City Cargo, one of the logistics companies operating in Saudi Arabia, with the aim that all goods movements in Saudi Arabia will be handled by City Cargo and goods movements in Indonesia will be handled by PT Indah Logistik. However, both companies experience problems with the cooperation agreement, namely legal certainty regarding the law that will govern the contract and the place of dispute resolution when there is a dispute in the future. The settlement of the cooperation agreement between the two companies, which are located in two countries with different legal systems, must be done carefully by considering all legal theories and principles to realize an agreement that can mutually benefit both parties.